Beverly Billingsly borrows a book - Stadler, Alexander (Silver Whistle/ Harcourt, 2002)
Beverly is thrilled to finally check out a book with her own library card, but when she accidentally keeps the book too long she worries that she'll have to pay a huge fine or go to jail.